A case of Langerhans cell histiocytosis mimicking child abuse - Başer, Şakire; Kaman, Ayşe; Zaimoğlu, Işıl; Gayretli-Aydın, Zeynep Gökçe; Aydın-Teke, Türkan; Kaygusuz, Umut; Gürkan, Asuman; Boduroğlu, Esin; Taşcı, Yasemin; Tanır, Gönül (The Turkish Journal of Pediatrics, 2016)
Langerhans cell histiocytosis is a rare non-malignant disease with clinical heterogeneity. The disease may present with various clinical findings and may imitate many other conditions. In this report we describe a 34-month-old girl who presented with chronic otitis and otorrhea, skull fracture, rash, vulvar edema, erythema and erosion in labia majors which initially suggested child abuse but the patient was diagnosed with Langerhans cell histiocytosis.
Keywords: Langerhans cell histiocytosis; child abuse